Early maltreatment is associated with greater risk of conduct problems and lack of guilt in adolescence. (May 2018) - Docherty, Meagan; Kubik, Joanna; Herrera, Carolina M.; Boxer, Paul
Abstract: Previous research indicates a link between childhood maltreatment and elevated conduct problems. Yet the literature is less clear on associations between maltreatment and callousness (e.g., lack of empathy or guilt). This is a critical gap given that callousness is a robust predictor of serious aggressive and violent behavior. We examine the association between substantiated maltreatment events in childhood and adolescence (up to age 13) and conduct problems and lack of guilt at age 14. We analyze self- and parent-report data along with official maltreatment records on 557 youth (50% female; 69% non-white) from a larger dataset (Longitudinal Studies on Childhood Abuse and Neglect; N  = 1354). Results of multinomial logistic regression models indicate that youth with histories of substantiated maltreatment events are more likely to have elevated conduct problems and decreased guilt at age 14, particularly if they experienced maltreatment before the age of four years old. Youth who exhibit conduct problems and also appear to lack guilt are more likely to have a personal history of substantiated maltreatment. We discuss our results in terms of their implications for theory and practice.